EDITORIAL - Vladimir Poroch; Daniela Moşoiu (Oncolog-Hematolog.ro)
Palliative care as a specialty or a subspeciality (competence)? ANIP’s position on the proper advancement of the palliative care concept in Romania and on the unified and comprehensive development of services at the national level